2020
DOI: 10.1016/j.annonc.2020.08.1834
|View full text |Cite
|
Sign up to set email alerts
|

1770P Clinical and epidemiologic aspects of patients with cancer and COVID-19 in a Brazilian cancer center

Abstract: patients, including CD86 (2.8-fold increase in classic monocytes, p¼0.06) and CCR2 (2.9-fold in intermediate monocytes, p¼0.17; 11-fold in non-classic monocytes, p¼0.03). Conclusions:In cancer patients presenting with severe SARS-CoV-2 positive pneumonia, the infection may cause a hypercoagulable state, as suggested by higher levels of D-dimer, and unleash a pro-inflammatory response. Marked CD4 + T lymphocytopenia and NK expansion may reflect lymphocyte exhaustion and dysregulated cytotoxicity. Monocyte activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Of the 105 patients, 69.52% required hospitalization and 33.3% were referred to the ICU. [12] More recently, a broader study conducted in private practices in Brazil showed a mortality rate of 16.7% among 198 cancer patients. However, it is a cohort of patients with better prognosis, including 29% of patients with breast cancer, 35% undergoing curative treatment, and 55% of outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 105 patients, 69.52% required hospitalization and 33.3% were referred to the ICU. [12] More recently, a broader study conducted in private practices in Brazil showed a mortality rate of 16.7% among 198 cancer patients. However, it is a cohort of patients with better prognosis, including 29% of patients with breast cancer, 35% undergoing curative treatment, and 55% of outpatients.…”
Section: Discussionmentioning
confidence: 99%